2022
DOI: 10.3390/children9030363
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the First COVID Lockdown on Accident- and Injury-Related Pediatric Intensive Care Admissions in Germany—A Multicenter Study

Abstract: Children’s and adolescents’ lives drastically changed during COVID lockdowns worldwide. To compare accident- and injury-related admissions to pediatric intensive care units (PICU) during the first German COVID lockdown with previous years, we conducted a retrospective multicenter study among 37 PICUs (21.5% of German PICU capacities). A total of 1444 admissions after accidents or injuries during the first lockdown period and matched periods of 2017–2019 were reported and standardized morbidity ratios (SMR) wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(30 reference statements)
1
0
0
Order By: Relevance
“…Our results could differ from literature reports, probably because our study was limited to patients treated at the Children's Orthopedic Department exclusively. Interestingly, our observation coincides with the Bruns N et al reports [18]. Based on a retrospective multicenter study among 37 pediatric intensive care units they found that SA increased in adolescent boys (standardized morbidity rate: 1.38) but decreased in adolescent girls (standardized morbidity rate: 0.56).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results could differ from literature reports, probably because our study was limited to patients treated at the Children's Orthopedic Department exclusively. Interestingly, our observation coincides with the Bruns N et al reports [18]. Based on a retrospective multicenter study among 37 pediatric intensive care units they found that SA increased in adolescent boys (standardized morbidity rate: 1.38) but decreased in adolescent girls (standardized morbidity rate: 0.56).…”
Section: Discussionsupporting
confidence: 92%
“…In 3 patients treated in a pandemic, the suicide attempt was the first manifestation of mental problems, none of these patients received psychiatric help before. The mean hospital stay in both groups was similar and amounted 17.75 days (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) for the group before and 16.2 days for the group after COVID-19, respectively. The most common SA in the group before COVID-19 was a jump from height.…”
Section: Resultsmentioning
confidence: 91%
“…However, less patients had to undergo head or neurosurgical procedures. 31 As expected, and in line with the previous reports, the number of cases drastically dropped to less than half of regular weekly presentations in our pED. 21,30 While during RP about 20% of mTBI were sustained in day care, kindergarten, or school, the drop was to a certain extent attributable to their closure.…”
Section: Discussionsupporting
confidence: 92%
“…This can also be confirmed in studies from Turkey and Germany. 37,38 At the same There was also a significant increase in accidents at home and domestic violence during the COVID-19 pandemic, with a simultaneous decrease in weekend and night-time trauma leading to mandible fractures. Due to reduced operating capacities and personnel shortages during the COVID-19 pandemic, a significant increase in days from trauma to operation was recorded.…”
Section: Discussionmentioning
confidence: 99%